Respuesta :

Step-by-step explanation:

(a) Fₙ₋₁ > 0, so Fₙ₊₁ > Fₙ.  Each term is bigger than the one before it, so the function is increasing, meaning the series will diverge to infinity.

(b) Fₙ₊₁ / Fₙ = (Fₙ + Fₙ₋₁) / Fₙ

Divide.

Fₙ₊₁ / Fₙ = 1 + (Fₙ₋₁ / Fₙ)

Rewrite the second fraction using negative exponent.

Fₙ₊₁ / Fₙ = 1 + (Fₙ / Fₙ₋₁)⁻¹

Take the limit of both sides as n approaches infinity.

lim(n→∞) Fₙ₊₁ / Fₙ = 1 + lim(n→∞) (Fₙ / Fₙ₋₁)⁻¹

Substitute with φ.

φ = 1 + φ⁻¹

Solve.

φ² = φ + 1

φ² − φ − 1 = 0

φ = [ -(-1) ± √((-1)² − 4(1)(-1)) ] / 2(1)

φ = (1 ± √5) / 2

Since the ratio can't be negative:

φ = (1 + √5) / 2